Rutting analysis of different rubberised stone mastic asphalt mixtures: from binders to mixtures. Issue 9 (2nd September 2022) - Subhy, Ayad; Lo Presti, Davide; Airey, Gordon; Widyatmoko, Iswandaru
Abstract : Stone Mastic Asphalt (SMA) has been broadly used on heavily trafficked roads and motorways in the UK due to its known stability and durability. In this study, several sets of SMA mixtures were produced using different rubberised bitumens, including a Fischer–Tropsch wax pre-treated rubberised bitumen. Properties associated with rutting were evaluated using both linear and nonlinear viscoelastic analyses, using different test methods such as the Strategic Highway Research Programme (SHRP), Shenoy rutting parameter, zero shear viscosity (ZSV) and multiple stress creep recovery (MSCR) tests. The rutting resistance of the resulting SMA mixtures was assessed using the Repeated Load Axial Test (RLAT). The addition of rubber was expected to enhance rutting resistance of these materials. The results indicated that among the binder rutting parameters assessed, the non-recoverable creep compliance (Jnr) computed from the MSCR test, showed the best correlation with the rutting resistance of the corresponding asphalt mixtures. Finally, a more fundamental analysis was provided by assessing the conditions of binder films that would be experienced in the mixtures. Highlights Rutting resistance of binders and mixtures are well correlated when the realistic strain conditions are taken into account SMA produced using rubberised bitumens resulted in highly rut resistant mixtures MSCR test can measure the rutting resistance of binders